2016
DOI: 10.1108/jfm-06-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the issue of naming rights of public sports facilities in Greece

Abstract: Purpose -The aim of this study was to conduct a primary examination of people's perceptions toward the concept of selling of naming rights for publicly owned sports facilities in Greece to explore the possibilities for this sponsorship practice to be introduced in the future. Design/methodology/approach -In all, 410 research participants filled out a questionnaire that focused on the level of acceptance, in relation to variations of agreements, and considering decision outcomes scenarios, as also on other nami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
0
4
0
8
Order By: Relevance
“…U prilog tvrdnji o sportskom karakteru Splita govori činjenica da su splitski sportaši osvojili 92 medalje na Olimpijskim of the cultural landscape, such as the sale of names (of stadiums 2 ), sports facilities and particularly their renaming has also been a focus of research (e.g. Boyd, 2000;Crompton and Howard, 2003;Leeds et al, 2007;Reysen et al, 2012;Church and Penny, 2013;Woisetschläger et al, 2014;Anestos et al, 2016;Medway et al, 2019), even though this process began in the 1970s (Rose-Redwood et al, 2010). Until then, toponyms with names motivated by sports (sports toponyms) were virtually not studied at all.…”
Section: Sports and The Citymentioning
confidence: 99%
“…U prilog tvrdnji o sportskom karakteru Splita govori činjenica da su splitski sportaši osvojili 92 medalje na Olimpijskim of the cultural landscape, such as the sale of names (of stadiums 2 ), sports facilities and particularly their renaming has also been a focus of research (e.g. Boyd, 2000;Crompton and Howard, 2003;Leeds et al, 2007;Reysen et al, 2012;Church and Penny, 2013;Woisetschläger et al, 2014;Anestos et al, 2016;Medway et al, 2019), even though this process began in the 1970s (Rose-Redwood et al, 2010). Until then, toponyms with names motivated by sports (sports toponyms) were virtually not studied at all.…”
Section: Sports and The Citymentioning
confidence: 99%
“…Χρησιμοποιήθηκε ως βάση το ερωτηματολόγιο των Chen & Zhang (2012) για τη μέτρηση των αντιλήψεων για τα δικαιώματα ονομασίας αθλητικών εγκαταστάσεων, της στάσης απέναντι στην εμπορευματοποίηση, της ταύτισης με την ομάδα, της ταύτισης με το γήπεδο, της στάσης προς τον χορηγό, και της πρόθεσης αγοράς προϊόντων του χορηγού. Για τα αποτελέσματα απόφασης αποδοχής της χορηγίας, υιοθετήθηκε η προσέγγιση των Kyle, Kerstetter & Guadagnolo (1999), τροποποιημένη στο πλαίσιο της χορηγίας δικαιωμάτων ονομασίας αθλητικών εγκαταστάσεων (Anestos, Gargalianos & Thamnopoulos, 2016). Από τις αναλύσεις διαπιστώθηκε ότι επηρέασαν σημαντικά και πρόβλεψαν τη στάση προς τον χορηγό οι αντιλήψεις για τη χορηγία, η αποτίμηση αποφάσεων αποδοχής της χορηγίας, και η στάση απέναντι στην εμπορευματοποίηση (η τελευταία, αρνητικά).…”
Section: προλογοςunclassified
“…The approach of Chen & Zhang (2012) was adopted to measure beliefs about naming rights, attitudes towards commercialization, team identification, stadium identification, attitude towards the sponsor, and purchase intentions for sponsor products. For the evaluation of the outcomes of sponsorship acceptance decisions, the approach of Kyle, Kerstetter & Guadagnolo (1999), as modified in the context of naming rights sponsorship (Anestos Gargalianos & Thamnopoulos, 2016) was adopted. From the analyses, it was found that sponsorship beliefs, evaluation of sponsorship acceptance decisions, and attitude towards commercialization had a significant effect on predicting attitude towards the sponsor, while attitude towards commercialization had a negative correlation with attitude towards the sponsor.…”
Section: προλογοςmentioning
confidence: 99%
See 2 more Smart Citations